Implementation of Strategic Management in Realizing Excellent Schools Based on Karawitan Arts - Yuni Ekawati; Syamsidar Binti Halim (JIEMAN: Journal of Islamic Educational Management, 2025)
The existence of traditional arts has become increasingly threatened by the rapid development of globalisation and the dominance of popular culture, which has significantly influenced the cultural preferences of younger generations. Numerous studies indicate that Indonesian students tend to show greater interest in foreign cultures than in their own local traditions. This condition highlights the urgent need for systematic and sustainable efforts to preserve traditional arts, particularly through the strategic role of educational institutions. SMP Negeri 4 Kalibagor has developed karawitan (traditional Javanese gamelan music) as a core element of its institutional identity and as a strategic instrument for achieving excellence as a school rooted in local wisdom. This study aims to describe and analyse the strategic management of karawitan-based school development in realising an excellent junior secondary school. Employing a qualitative approach, this field research collected primary data through in-depth interviews, supported by secondary data obtained from observation and documentation. Data validity was ensured through source triangulation, while data analysis was conducted using an interactive model consisting of data reduction, data display, and conclusion drawing. The findings reveal that SMP Negeri 4 Kalibagor has positioned karawitan as a strategic school policy, having carefully considered conducive internal and external environmental conditions. The development of karawitan is implemented systematically through strategic management stages, including the formulation of vision and mission, internal and external environmental analysis, determination of strategic objectives, strategy formulation and implementation, policy and target setting, as well as continuous monitoring and evaluation. This strategic policy not only serves as a concrete effort to preserve local cultural heritage but also functions as a means of building the school’s competitive advantage at the basic education level, thereby contributing to the advancement of strategic management studies in education grounded in local wisdom.